Residual bioburden in reprocessed side-view endoscopes used for endoscopic retrograde cholangiopancreatography (ERCP) - Ubhayawardana, D. L. N. L; Kottahachchi, J; Weerasekera, M. M; Wanigasooriya, I. W. M. P; Fernando, S. S. N; De Silva, M (My University, 2013)
Background and study aim: Worldwide some endoscopyunitsroutinelycontinuetousemanual reprocessing techniques for disinfection of sideview endoscopes. The aim of this study was to evaluatetheoutcomequalityofmanualreprocessing techniques for removal and inactivation of the bioburden from side-view endoscopes used for endoscopic retrograde cholangiopancreatography (ERCP) in a tertiary referral endotherapy unit in Sri Lanka. Methods: 102 samples obtained from two different flexible side-view endoscopes (Olympus TJF Q 180V and Olympus TJF 160R) were tested for microbial growth. Three samples were collected each time; one swab from the tip before and another after manual reprocessing.The third sample was collected by flushing the working channel with sterile normal saline after manual reprocessing. Microorganisms were identified by culturing the samples. Result
Keywords: Residual bioburden; Endoscopic Retrograde Cholangiopancreatography